Indicative role of pine radial growth for assessing the dynamics of the state of upland bogs Belarusian Polesie - Matsiusheuskaya, Katsiaryna V. (Journal of the Belarusian State University. Geography and Geology, 2023)
The aim of the study was to investigate the peculiarities of the reaction of pine trees (Pinus sylvestris L.) growing in one of the upland bogs in the Belarusian Polesie, the conditions of which can be regarded as pessimal in relation to tree plantations, to the change of regional climate as a leading environmental factor. The object of the study was a pine-ledum-sphagnum forest. The subject of the study was the absolute minimum and maximum radial growth of currently growing pine stands aged up to 305 years. The main methods used in dendrochronology and dendroclimatology (the method of comparison and comparative analysis) were applied to achieve the goal. The sequence of probable changes in hydration and watering conditions in Belarusian Polesie in the Holocene was traced for the period of absence of instrumental observations of climate characteristics (amount of solar radiation, air temperature, precipitation) and according to the data of the longest meteorological station in the region (Vasilevichi). It was established that the change in natural conditions of the region, caused by the influence of natural and anthropogenic (drainage reclamation) factors, expressed in the change of edaphohydrological conditions, is manifested in the multidirectional dynamics of wood diameter growth in pine stands growing in the upland bog.